Two stories, one vision: A plea for an ecological turn in intercultural communication. Issue 4 (1st October 2016) - Mendoza, S. Lily; Kinefuchi, Etsuko
ABSTRACT: This paper calls for a "fifth moment" in the field of intercultural communication that re-examines modern culture's values, beliefs, and assumptions about human being in the world and the role of such in fomenting today's ongoing planetary-wide ecological crises. To conduct this re-examination, we turn to ethnoautobiography, a framework rooted in story and in the indigenous paradigm. We raise deep questions regarding the default assumptions of a discipline ensconced almost exclusively within the monocultural logic of modern culture and civilization. We end by posing key problematics that we deem crucial for renewing the discipline toward contemporary relevance, ecological awareness, and responsibility.